Academic Speaking Students’ Efforts in Minimizing Their Lack of Self- Confidence - Novita Kusuma Ningrum; Listyani Listyani (Prominent, 2022)
The existence of self-confidence is needed and related with students’ academic achievement, which in this context of the study is speaking skills. Speaking skills are the language learning aspects that are also crucial for students to master to have good communication. Unfortunately, speaking skills cannot be mastered because of the lack of self-confidence that is commonly faced by EFL learners. By seeing this reality, the researcher tried to identify the causes of the lack of self - confidence faced by Academic Speaking students (FLA-UKSW) and the efforts that the students implemented to overcome their lack-of self-confidence. This study used a qualitative method in collecting data. The data were collected from thirty-three Academic Speaking students using open-ended questions and semi-structured interviews. The findings indicated the causes of the lack of self-confidence were fear of making mistakes, lack of speaking skills formally, public speaking anxiety and personal experience influenced. The efforts used by students were talking in front of a mirror, practicing pronunciation, rehearsing with friends, mastering materials, making notes, watching YouTube videos. The result of these findings hopefully helped students who are dealing with self-confidence in academic context specifically in speaking skills.